Pengaruh Persepsi Kegunaan, Persepsi Kemudahan, dan Persepsi Risiko Terhadap Keputusan Penggunaan BRI Mobile (BRImo) (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Adam, Adam; Wahono, Budi; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The development of information technology is running fast along with the increasing needs of society. The use of smartphones has become commonplace for every individual in their daily activities. With the high level of smartphone adoption by the public, the banking sector is taking advantage of this trend by launching mobile banking services. BRI is one of the banks that provides mobile banking-based services. In 2019, BRI launched the BRImo application which is a development of the previous mobile banking platform. The purpose of this study is to determine whether users' decisions to use BRImo are influenced by perceived danger, perceived convenience, and perceived utility. The research methodology employed here is Explanatory Research utilizing quantitative approaches. The study focuses on active students enrolled at the Islamic University of Malang as its population.. The number of samples used was 96 respondents which was determined using the Slovin formula. In testing the research hypothesis, multiple linear regression analysis was used with the SPSS 22 analysis tool. The test results showed simultaneously and partially that perceived usefulness (X1), perceived convenience (X2), and perceived risk (X3) had a positive and significant effect on usage decisions  (Y). Keywords: Perception of Usefulness, Perception of Convenience, Perception of Risk, Decision to Use